1992
DOI: 10.1093/geronj/47.5.m137
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medications by Persons 65 and Over: Data From the Established Populations for Epidemiologic Studies of the Elderly

Abstract: Data were analyzed from household interviews of four population-based cohorts comprising the Established Populations for Epidemiologic Studies of the Elderly to estimate the prevalence of prescription and nonprescription medication use among community-living elderly and to examine sociodemographic and health factors related to medication use. Prescription drugs were used by 60-68% of men and 68-78% of women. Nonprescription drugs were used by 52-68% of men and 64-76% of women. Use of prescription medications g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
130
0
20

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(166 citation statements)
references
References 0 publications
16
130
0
20
Order By: Relevance
“…A maioria dos estudos de utilização de medicamentos relata o uso de um número médio de quatro medicamentos por idoso 4,5,6,7,8,9 . O perfil de utilização de medicamentos por idosos acarreta em gasto elevado com a aquisição dos mesmos em comparação ao observado nas demais faixas etárias 10,11 .…”
Section: Introductionunclassified
“…A maioria dos estudos de utilização de medicamentos relata o uso de um número médio de quatro medicamentos por idoso 4,5,6,7,8,9 . O perfil de utilização de medicamentos por idosos acarreta em gasto elevado com a aquisição dos mesmos em comparação ao observado nas demais faixas etárias 10,11 .…”
Section: Introductionunclassified
“…[1][2][3][4] The most plausible mechanism by which aspirin prevents ischemic events is by irreversible inhibition of the isoenzyme cyclooxygenase-1 (COX-1). 5 In the United States, nonaspirin nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used 6 for their analgesic, anti-inflammatory, and antipyretic effects. These effects result primarily from inhibition of COX-2 7 and reduced prostaglandin production.…”
mentioning
confidence: 99%
“…93 Aging is associated with a decline in renal function, 94 and both polypharmacy and drug utilization in general is remarkably high in this segment of the population. 95,96 In general, it is likely that both altered pharmacokinetic and pharmacodynamic factors contribute to the risk of opioidrelated cognitive dysfunction in this patient group. 97 Several studies have documented the use of lower doses of opioids in the elderly.…”
Section: Pathophysiology Of Opioid-associated Cognitive Dysfunctionmentioning
confidence: 99%
“…• Educate family regarding recognition of potential neurotoxic features such as myoclonus 106 • Objectively monitor cognition 108,111 • Adjust dose in elderly patients 96,97 • Discontinue or minimize use of all unnecessary medications, especially other psychotropics 4 • Adjust dose for impaired renal function [93][94][95] • Maintain adequate hydration and use diuretics cautiously 4 • Perform a multidimensional assessment 127,128 • Identify poor prognosticators for pain control: neuropathic and incidental pain, somatization, tolerance, and addiction history 125 • Optimal utilization of other therapies e.g., appropriate use of adjuvant and other therapies, maximize nonpharmacologic interventions 67 • Adopt a proactive approach: early intervention with management strategies to possibly avert a full-blown delirium syndrome 17 patient group noted a decrease of approximately 60% in the chart recordings of agitated impaired mental status in association with a practice change of increased opioid rotation, hydration, and objective cognitive monitoring. 133 An open prospective study of hospice patients by Maddocks et al found a significant improvement in mental state in patients with morphine-associated delirium, who were switched to oxycodone.…”
Section: Table 6 Proposed Strategies To Prevent Opioid-induced Cognitmentioning
confidence: 99%
See 1 more Smart Citation